Newborn with Abnormal Noisy Breathing– Accidentally Finding of Aryepiglottic Cyst - Salleh, Mohamad Najib; Ab Hamid, Suzina Sheikh; Mohamad, Hazama (International Journal of Human and Health Sciences (IJHHS), 2022)
There are many causes of laryngeal stridor in infants and young children, in which congenital laryngeal cyst (CLC) is one of the possible causes. CLC is a rare cause of neonatal upper airway obstruction, which leads to serious morbidity and mortality if diagnosis and treatment are delayed. The aetiology of this pathology is not clear since it can be a congenital or acquired condition. CLC frequently promotes respiratory tract obstruction in neonates, resulting in inspiratory stridor and shortness of breath. The gold standard for diagnosing CLC is still through direct laryngoscopy. The laryngeal ultrasound and CT scan can help clarify things, especially if there's a question about something else pathologically. Surgical, endoscopic, or external approaches are used to treat these cysts. The best way to prevent recurrence is to obliterate the cysts. Small cysts can be removed endoscopically, but larger cysts must be approached externally. International Journal of Human and Health Sciences Supplementary Issue: 2022 Page: S15